2019
DOI: 10.1186/s12960-019-0363-7
|View full text |Cite
|
Sign up to set email alerts
|

For more than money: willingness of health professionals to stay in remote Senegal

Abstract: Background Poor distribution of already inadequate numbers of health professionals seriously constrains equitable access to health services in low- and middle-income countries. The Senegalese Government is currently developing policy to encourage health professionals to remain in areas defined as ‘difficult’. Understanding health professional’s preferences is crucial for this policy development. Methods Working with the Senegalese Government, a choice experiment (CE) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
5
18
2
Order By: Relevance
“…Unlike several studies showing that financial incentives were not found to be most powerful policy levers [13,26,28,31,33,36,38,44]. However, our findings conformed that monthly income had a significant impact on the job choices of undergraduate health students, similar with other studies [10,37,45].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Unlike several studies showing that financial incentives were not found to be most powerful policy levers [13,26,28,31,33,36,38,44]. However, our findings conformed that monthly income had a significant impact on the job choices of undergraduate health students, similar with other studies [10,37,45].…”
Section: Discussionsupporting
confidence: 87%
“…This is particularly true for medical and nursing students, who are often disappointed by the gap between what they have been taught to do, often based in a tertiary hospital infrastructure, and the availability of equipment in rural health facilities where they are expected to work after the graduation. These results are consistent with those from other DCEs [13,35,37,38,41]. Also, a review paper on health worker's motivation and retention indicates that the improvement of hospital infrastructure and resource available could increase retention [42].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…29 A study from Senegal reported that the provision of a permanent contract was the most important factor for retaining employees in rural and challenging regions, following the availability of necessary equipment in working facilities and the provision of training opportunities. 30 In the mining industries, the situation may be similar. The satisfaction of temporal nancial needs as well as comfortable working environments/conditions, including a balanced and proper salary and guaranteed sustainability of these working conditions, should be fundamental for both individual workers and organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The capitation system that is used as the basis for payment of medical services is difficult for doctors who work in remote areas, especially with diffuse geographical and demographic conditions. A difficult work environment and does not guarantee social life is also a separate obstacle (Laksono, Nantabah and Wulandari, 2018;Bertone, Lurton and Mutombo, 2016;Honda et al, 2019;Mashange et al, 2019).…”
Section: Discussionmentioning
confidence: 99%